POOR HOUSEHOLDSâ CREDIT ACCESSIBILITY: THE CASE OF RURAL VIETNAM - Dao, Ha Thi Thieu; Kim, Nguyen Thien; Mai, Nguyen Thi (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
This paper examines determinants of accessibility to rural poor households in Vietnam from the viewpoint of policyÂ makers, credit institutions and poor households. From supply side annual report of provider will be cited, from demandÂ side, VHLSS primary data provided by GSO will be used. Beside that semi-structured questionnaire survey will beÂ conducted to collect qualitative information. Logit model is employed to investigate the determinants of their outstandingÂ loan. The quantitative modelâs results express that age, education, regional differentiation, industrial differentiation,Â land, asset affect to credit access of poor households. The qualitative analysis finds out some recommendations forÂ adjustment the poverty reducing credit policy